Experiential Religion: A Faith Formation Process for Children with Autism - Swanson, Susan (Journal of religion, disability & health, 2010)
Families of children diagnosed with autism face multiple challenges in finding faith formation opportunities that are sensitive to their child's unique communication, social-emotional, cognitive, and sensory needs. By embracing the biblical understanding of the word “know”, we are reminded that “knowing God” calls forth a “whole-body way of knowing” that transcends our cognitive understanding of who God is. For children with autism, this knowing means creating opportunities in which they come to know God through experiencing God. Using focusing procedures, the construct of experiential religion proposes that it is only in the primacy of feelings and within the process of experiencing that a bodily felt relating to the divine is possible (Shea, 1987). A faith-formation process is proposed that integrates the focusing dynamic with best practices in teaching children with autism.